(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Juggling between professional and personal space the workforce today is stressing themselves as they have to meet the demanding needs asked by their clients, boss and colleagues at times and also family, friends and relationships as well. Especially the employees working in a BPO industry should provide all the deliverables within the stipulated time given to them. The present research is working on the lines to study and understand the relationship between leisure activities and quality of work life among general shift BPO employees as the shift timing in which these employees work provide them with some space to breath between work, family and the personal front. This research should be able to help us find the association between the two variables that are considered. Based on the above stated points the objective of the study is framed so as to study the relation between leisure activities and quality of life among general shift BPO employees. A total of 60 BPO employees both (30 men and 30 women) belonging to the age group of 19-30 year working in general shift were considered for the study. The exploratory design was adopted. To measure leisure activities - The Victoria Longitudinal Study Activities Questionnaire developed by Jopp Hertzog (2010) was used and to measure work life balance - Quality of Work-Life Scale, developed by Santhosh Dhar, Upinder Dhar, Rishu Roy (2005) was administered to all the participants. The results indicate that there is no significant relation between leisure activities and quality of life among general shift BPO employees.